Reliability-based design of composite structures under dynamic behaviour - Carlos Conceição António (2009)
An optimisation model for maximization of structural reliability of compositestructures under dynamic loading conditions is proposed. The failure probability is obtainedusing a procedure based on level 2 reliability analyses adapted for dynamic response.Material properties of the ply are considered normal random variables. The optimisationprocess is based on a Hierarchical Genetic Algorithm where a master population evolvestogether with a net of slave sub-populations. The proposed topology aims to link the MostProbable failure Point (MPP) search with the maximisation of structural reliability.